Spectrophotometric Determination of Carbofuran with Diazotized Benzidine in Environmental Water Samples - Baghdad Science Journal (مجلة بغداد للعلوم, 2016)
A simple, rapid, accurate and sensitive spectrophotometric method has been developed for the determing carbamate pesticides in both pure and water samples. The method is appropriate for the determination of carbofuran in the presence of other ingredients that are usually available in dosage forms. The effect of organic solvents on the spectrophotometric properties of the azo dye and the structure of the resulting product have also been worked out and it is found to be 1:1 benzidine :carbofuran. The method can be successfully applied to determination of carbofuran in water samples. The method is based on diazotization of Benzidine (4, 4 – diamino biphenyl) with sodium nitrite and hydrochloric acid followed by coupling with carbofuran in alkaline medium to form a yellow colored azo dye having the absorption maximum at 429nm against reagent blank solution. Beer’s law is obeyed in the concentration range of (0-14) ?g of 10mL carbofuran. Molar absorptivity of 1×104 L.mol-1.cm-1 which depend on the concentration level of carbofuran.